The macroeconomic impact of recent political conflicts in Africa: Generalized synthetic counterfactual evidence - Samba Diop; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2021)
This paper measures the macroeconomic impact of recent political crisis, protest and uprisings in Africa with the generalized synthetic control method and evaluates the role played by natural resource dependence on the modulation of the impact. We find that political crisis, protests and uprisings have a significant and negative impact on economic growth while the impact is positive on investment and price level. For economic growth, the deviation of the actual series from the counterfactual is negative, instantaneous, persistent and highly significant; indicating non-negligible costs of the shock. Indeed, dependence on natural resources amplifies the negative effect of political crisis, protests and uprisings on GDP. Finally, the more the treated country depends on natural resources, the more it becomes resilient from the investment losses caused by political crisis.
Keywords: F52; K42; O17; O55; P16; 330; political conflicts; economic growth; Africa